Entrepreneurial intentions: a 20-year global bibliometric journey / Nor Faiz Azizan and Hardy Loh Rahim - Azizan, Nor Faiz; Rahim, Hardy Loh (Universiti Teknologi MARA, 2025)
Over the past two decades, research on Entrepreneurial Intention (EI) has emerged as a critical field, providing insights into the cognitive processes underpinning entrepreneurial activities. This paper presents a comprehensive bibliometric analysis of two decades of global EI research, utilizing over 5,000 publications indexed in Scopus. Using VOSviewer as a visualization tool, the current study examines trends in publication patterns, identifies key contributors, and highlights thematic areas, emphasizing the importance of frameworks such as the Theory of Planned Behavior (TPB) and entrepreneurial self-efficacy in influencing entrepreneurial intention (EI). Findings indicate a rise in interdisciplinary research, with substantial contributions from business, social sciences, and psychology. Additionally, the study reveals the impact of education, gender, and cultural contexts on EI, offering a roadmap for future research in entrepreneurial education and policy development. This research serves as a valuable resource for academics, educators, and policymakers aiming to promote entrepreneurship globally.